Optimizing the Role of Mosque Youth in Enhancing Social and Religious Awareness Among Youth - Masrifatin, Yuni; Rahmawati, Lilis; Setiyawan, Nofika Dwi; Wahyuningtyas, Asfiana; Azmi, Mu’arfatul; Rizqi, Aditya Arum Wijaya (Bisma : Bimbingan Swadaya Masyarakat, 2023)
This study examines the role of mosque youth in enhancing social and religious awareness within their communities. The research utilizes a Participatory Action Research (PAR) approach, emphasizing community involvement in the development and implementation of mosque youth programs. The study was conducted in several mosques, where mosque youth leaders participated in leadership training, religious programs, and community service activities. Findings suggest that mosque youth engagement in structured religious education and social initiatives contributes significantly to their religious and social development. The leadership training provided to mosque youth leaders helped improve organizational management and increased participation in mosque-based activities. Furthermore, the integration of social media into mosque youth programs proved effective in reaching a broader audience, particularly the younger generation. Despite challenges such as limited resources and varying levels of interest, the study demonstrates that mosque youth can play a key role in fostering social responsibility and religious awareness. The results highlight the potential for mosque youth to contribute to both the spiritual and social transformation of their communities.